Safety assurance behaviour on online purchase among Orang Asli (indigenous people) in Malaysia - Hanapi, Noor Hazwani; Muhammad Arif, Afida Mastura (Human Resource Management Academic Research Society, 2023)
Technology has transformed the shopping experience for consumers, and Malaysia's high Internet penetration rate has fueled the rapid expansion of the local online shopping market in recent years. In addition to the convenience of online shopping, it also presents a new frontier for consumer complaints and complex consumer protection issues. The purpose of this study was to investigate the indigenous consumer’s (Orang Asli) online purchase safety assurance behaviour in Bera, Malaysia. The data were collected through a self-administered questionnaire distributed among 150 respondents, following which statistical analysis was performed inclusive of descriptive analysis and Pearson’s correlation. The outcome revealed that awareness, worry and media of consumer education pose a positive and significant relationship with safety assurance behaviour, whereby worry was denoted as the highest correctional variable. The findings of this study are beneficial for the government to educate consumers, especially among Orang Asli, regarding safety assurance behaviour in online purchases.